A Complicated Opioid Overdose: A Simulation for Emergency Medicine Residents - Michael P. Keenan; Keith A. Schenker; Matthew J. Sarsfield (Association of American Medical Colleges, 2017)
Introduction Opioid abuse is a growing problem in the United States. As a result, emergency medicine physicians often use naloxone to reverse opioid overdoses. While normally a safe drug, one potential complication of the antidote's use is flash pulmonary edema. This simulation was created after a patient followed the clinical course described after an opioid overdose. Methods This simulation utilized a high-fidelity simulator to expose resident emergency medicine physicians to flash pulmonary edema secondary to naloxone administration. The simulation involved a 31-year-old male patient presenting with agonal respirations following an opioid overdose. The residents managed the patient appropriately with naloxone. However, he developed progressive dyspnea. The residents soon discovered that the patient was in flash pulmonary edema. They managed his airway, provided mechanical ventilation, and considered extracorporeal membrane oxygenation. Results When this simulation was run for emergency medicine residents at SUNY Upstate Medical University, the learners felt that it was highly useful, and that it expanded their knowledge in this field. Out of 17 learners, the average rating to the question of: "[This simulation] added to my understanding of key concepts and helped the session meet the objectives" was 4.6 on a 1-5 Likert scale. Discussion This simulation is a practical method by which many institutions can help to further physician knowledge on opioid overdose complications. It is relatively straightforward to run, and the educational yield is high.